2022
DOI: 10.1038/s41588-021-01009-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determinants of human gene regulatory elements

Abstract: DNA can determine where and when genes are expressed, but the full set of sequence determinants that control gene expression is unknown. Here, we measured the transcriptional activity of DNA sequences that represent an ~100 times larger sequence space than the human genome using massively parallel reporter assays (MPRAs). Machine learning models revealed that transcription factors (TFs) generally act in an additive manner with weak grammar and that most enhancers increase expression from a promoter by a mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
128
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(144 citation statements)
references
References 73 publications
16
128
0
Order By: Relevance
“…Whereas R3 facilitates the activities of R1 and R2 to a similar degree regardless of Rm/R4 coincidence, Rm and R4 function in a context-dependent manner, each partially redundant to the other. Interestingly, Sahu and colleagues recently used a STARR-seq method to show that four out of the five MYC SE constituents have no detectable enhancer activity in HepG2 cells (Sahu et al, 2022). It is unclear whether these four non-functional elements are required for full SE activity, but it raises the possibility that facilitators could be a common feature of SEs.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas R3 facilitates the activities of R1 and R2 to a similar degree regardless of Rm/R4 coincidence, Rm and R4 function in a context-dependent manner, each partially redundant to the other. Interestingly, Sahu and colleagues recently used a STARR-seq method to show that four out of the five MYC SE constituents have no detectable enhancer activity in HepG2 cells (Sahu et al, 2022). It is unclear whether these four non-functional elements are required for full SE activity, but it raises the possibility that facilitators could be a common feature of SEs.…”
Section: Discussionmentioning
confidence: 99%
“…The choice to focus on the range from À350 to +50 bp was motivated by our previous study of human promoters, which indicated that most of the relevant information for promoter function is generally contained within this range (van Arensbergen et al, 2017). This definition of promoters is longer than that of core promoters (which are usually only $100-bp long) as was used in most previous enhancer reporter assays (Ohler et al, 2002;Haberle et al, 2019;Inoue and Ahituv, 2015;Klein et al, 2020;Davis et al, 2020;King et al, 2020;Sahu et al, 2021). We considered this to be important because the extra regulatory information contained in those additional sequences may be relevant for interactions of the promoters with CREs.…”
Section: Experimental Designmentioning
confidence: 99%
“…In order to address this issue, we systematically tested the compatibility of thousands of combinations of candidate CREs (cCREs) and promoters using MPRAs. We used plasmid-based MPRAs because they are highly scalable (Inoue and Ahituv, 2015;van Arensbergen et al, 2019;Sahu et al, 2021) and because episomal plasmids provide an isolated context that minimizes confounding effects of variable chromatin environments and differences in 3D folding. However, so far, MPRAs have mostly been used to assess the activity of single elements, either as enhancers or as promoters (Inoue and Ahituv, 2015;van Arensbergen et al, 2017;Arnold et al, 2013;Klein et al, 2020;Davis et al, 2020;King et al, 2020), except for one recent study that tested combinations of synthetic elements (Sahu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence patterns are generated from the attribution scores of DNA sequence toward enhancer activity in an investigated cell line. We observed that the generated sequence patterns matched with TF motifs such as CREB, JUN, YY, ETS, and IRF, which related to enhancer activity and were enriched in enhancers [39].…”
Section: Enhancer Activity Prediction (Eap)mentioning
confidence: 81%